Good practices handbook for Integrating urban development and wetland conservation - WWT Consulting (2018)
This Handbook provides guidance to individuals, businesses, organizations or government involved in the design, planning, management and/or construction of urban wetlands. By showcasing examples from all over the world and sharing valuable experiences, it is hoped that the best practice principles, illustrated throughout the handbook, will be widely adopted. Whether it is a recognised wetland of international importance or ahumble pond in the middle of a busy park, good planning, design and management practices go hand in hand with healthy wetlands, and we are collectively responsible for safeguarding the health of our wetlands in order to guarantee the vital role that they play in our lives. The Handbook has been produced as a result of discussions held at the “Good Practices for Integrating Urban Development and Wetland Conservation Workshop” in Changshu (China) in January 2018.